High-temperature and high-resolution crystallography of thermostable copper nitrite reductase. Issue 30 (7th January 2015) - Fukuda, Yohta; Inoue, Tsuyoshi
Abstract : The structure of thermostable copper nitrite reductase in complex with nitrite was determined at 320 K. Abstract : The 1.55 Å resolution thermostable copper nitrite reductase structure at 320 K displayed a near-bidentate binding mode of nitrite distinct from a monodentate mode in a cryogenic structure. To our knowledge, this is the first case in which the difference in substrate binding modes between cryogenic and high-temperature structures has been visualized by crystallography.